2010
DOI: 10.4018/jeco.2010100104
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting e-Payment Adoption in Nigeria

Abstract: The payment system of a country plays a crucial role in its economy; however, despite the benefits of e-Payment and efforts by financial authorities, Nigeria still has a low e-Payment adoption rate. In this regard, there is an urgent need to investigate the factors that affect individuals’ intention to adopt e-Payment. Drawing on the unified theory of acceptance and use of technology (UTAUT) model, this paper develops a theoretical model for e-Payment adoption in Nigeria. Additionally, a survey was conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 41 publications
5
42
0
2
Order By: Relevance
“…The banks and electronic switching companies have also rolled out infrastructure to facilitate the use of e-payments." In spite of such various efforts and commitments, banking reports and academic studies indicated that the adoption of ebusiness payment systems in Nigeria continue to be low and unimpressive (Babalakin & Co;, Agbada, 2008Akpan, 2008;Gholami et al, 2010;Ayo et al, 2011)…”
Section: Wwwintechopencommentioning
confidence: 99%
See 4 more Smart Citations
“…The banks and electronic switching companies have also rolled out infrastructure to facilitate the use of e-payments." In spite of such various efforts and commitments, banking reports and academic studies indicated that the adoption of ebusiness payment systems in Nigeria continue to be low and unimpressive (Babalakin & Co;, Agbada, 2008Akpan, 2008;Gholami et al, 2010;Ayo et al, 2011)…”
Section: Wwwintechopencommentioning
confidence: 99%
“…It is worth pointing out that Nigeria is largely a cashbased country in which a high percentage of its economic transactions are conducted with cash (Gholami et al, 2010;Ayo et al, 2011). This is partly due to the country's socio-cultural imperatives (Ifinedo, 2005b) and the embryonic development of e-business payment systems acceptance among businesses and the population.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 3 more Smart Citations